Natural Resource Dependence and Monopolized Imports - Rabah Arezki; Ana Margarida Fernandes; Federico Merchán; Ha Nguyen; Tristan Reed (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper explores the effect of natural resource dependence on market concentration of imports. Using a new panel database for importing firms in developing and emerging market economies, the paper shows that higher natural resource dependence is associated with larger market concentration of imports and with higher tariffs. The effect on the concentration of imports is found to be more pronounced for exporters of 'point-based' resources, imports of primary and consumption goods than for capital goods and is associated with higher domestic prices and lower consumption expenditure. Results suggest a novel channel for the resource curse stemming from the "monopolization" of imports.
Keywords: D20; F10; L10; O10; Q00; 330; imports; market concentration; natural resources; resource curse